The Analysis of Nursing Problems in Mothers with Hyperemesis Gravidarum at RS NU Banyuwangi - Rahmawati Raharjo; Mahmud Hakim (Institute of Computer Science (IOCS), 2021)
Hyperemesis gravidarum is vomiting that occurs in early pregnancy until the gestational age of 20 weeks, where sometimes vomiting occurs so intense and interfere with daily activities. Hyperemesis gravidarum can harm the health of the mother that can cause a weight loss of more than 5% and lead to metabolic disorders. This research is a descriptive retrospective cross-sectional design with data collection on the patient's medical record for a year in 2019. This research was conducted at the HOSPITAL of Nahdlatul Ulama Banyuwangi. In this study found pregnant women with hyperemesis gravidarum based on the age of the mother most of the high experienced by pregnant women in the age group <25 years as many as 30 people (68,2%). Based on the parity of the most high experienced by pregnant women in the group of parity primigravida as many as 30 people (68,2%). Based on the level of education of the mother most of the high experienced by pregnant women who have a high SCHOOL education that is as much as 18 people (40,9%). The results of the statistical test of this study concluded with the results of the test of SPSS version 17 the obtained value of the largest there is on the issue of nursing disorders of fluid balance with the amount of 52,3%, followed by disorders of nutrition with the number of the 31.8%, and the last is hipertermi with the amount of 15.9%. Based on the results of the analysis of nursing assessments of hyperemesis gravidarum cases experienced by pregnant women (research samples), three nursing diagnoses or nursing problems were found including fluid balance disorders, nutritional balance disorders and hyperthermia. The nursing problems experienced by the sample are in accordance with the implementation of the diagnosis according to the IDHS. From the three diagnoses, a priority nursing diagnosis was obtained, namely fluid balance disorders. From nursing diagnoses that appear, interventions that can be performed on pregnant women are adjusted to clinical signs so that the goal to overcome the problems that occur can be achieved.